Pharmacological Benefits of Miswak Users and Its Impact on COVID-19 Patients – A Review: Life Sciences-Biotechnology for prospective medical science - Sumayya Rehaman (International Journal of Life Science and Pharma Research, 2022)
In the quest of vaccine/medicine for the Covid-19, a major challenge for the intact community on the Earth, the scientists are eagerly involved in the struggle to achieve a new vision in the field of drug discovery. In meantime, we have also forgotten the usage of preexisting medicinal plants and searching the treasure in the dark. To enlighten on, and to dig the hidden boon, this review paper highlights Salvadora persica, a miracle twig’s various medicinal properties and also about major influence against the viral activities and the asymptomatic conditions in Covid-19 patients of miswak users. It also highlights the literature evidence on the isolated chemical metabolites present in the root and stem of the tree which emphasize its beneficial effects against the bacterial and viral load. This review will hopefully encourage the upcoming search to widen their research on miswak in nCoV of Covid-19 patients and the common people need to document for the regular usage of miswak with brushing the teeth, to attain its properties.